Disclosure Integration of Lean Six Sigma Principles in Sustainable Supply Chain in Poultry Industry - Ratna Yulia Kusumastuti; Heti Mulyati; Gendut Suprayitno (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
The poultry industry has been in the spotlight for its enormous potential economic development. However, poultry industry is still not implementing the concept of sustainability properly. There are still many wastes that have not been managed properly and there are still many problems in the supply chain that require more systematic handling. Many studies have shown that the implementation of Lean Six Sigma (LSS) and sustainability has positive results on the company's bottom line performance. This research tried to integrate the application of LSS principles and sustainability along the supply chain in the poultry industry in Indonesia. Data were collected from 4 listed poultry firms in Indonesia. The research method used SEM PLS with SmartPLS software. The results showed that supply chain security management system disclosure as the principle of LSS had a positive effect on the collaboration of supply chain disclosure and collaboration of supply chain disclosure had a positive effect on sustainability. The results also showed that risk management disclosure had a negative effect on the collaboration of supply chain disclosure and economic sustainability had a negative effect on environmental sustainability, but social sustainability had a positive effect on environmental sustainability. Based on the results of this study, there is a need to improve supply chain security management system and supply chain collaboration in order to advance sustainable poultry industry.